DINAMIKA PENYELENGGARAAN IBADAH HAJI INDONESIA DI RAB SAUDI - Faiz Resha Majid (ISIPOL HI 15 UMY 287, 2015)
*287 This scientific work is the result of a review of the study of international relations, namely the form of diplomacy. With the case of the dynamics of Indonesian Hajj in Saudi Arabia. This research method is a way to collect the data available there, either in the form of supporting books related, related websites, as well as interviews with informants. Relations between Indonesia and Saudi Arabia, especially in the organization of the pilgrimage has existed a long time. During this time there are several factors that often affect the implementation of the Hajj. In the organization of the Hajj by Indonesia in Saudi Arabia there is a driving factor and inhibiting factor that in fact impact on performance in the organization of the Hajj. The existence of things and factors associated demanded Indonesia to be able to react to it. To be able to provide even better then perform multi-track diplomacy Indonesia to Saudi Arabia as the organization of the Hajj, the implementation of Indonesia to cooperate with parties such as the relevant ministries in fields such as religion, health, transportation; Hajj travel agencies, religious organizations, and members of the media